The influence of science and technology on the foundation phase policies of the BRICS associate countries: A comparative study - Julia Correia; Deon Vos; Louw De Beer (Perspectives in Education)
The pervasive influence of science and technology globally necessitates thoroughly examining its impact on education systems as policymakers face the daunting task of recalibrating educational frameworks for contemporary professional requirements. These changes affect learning, teaching and institutional operations, with innovation becoming a cornerstone of educational reform. This study applies a qualitative comparative document analysis within  an interpretivist paradigm to delve into the ramifications of the modern wave of globalisation, fuelled by scientific and technological advancements, on the foundation phase (FP) education policies of the countries aligned with the intergovernmental organisation called BRICS. Data was gathered from policy documents, curricula and academic literature. The analysis focused on identifying science and technology integration patterns into the FP curricula in these countries. Findings reveal distinct national approaches to incorporating science and technology in early education. Brazil emphasises digital literacy through its BNCC policy, while China integrates robotics and AI from the early years. Russia and India have introduced computational thinking in primary education, and South Africa is piloting coding and robotics in the foundation phase. Though diverse approaches are followed, these reforms highlight a shared recognition of the need to cultivate creativity, critical thinking and problem-solving from a young age. The study sheds light on the transformative potential of science and technology in reshaping educational paradigms in the BRICS countries. By highlighting the complex factors involved, the study advances the scholarly discourse. It offers pragmatic insights for policymakers and stakeholders seeking to navigate the complexities of educational reform in an increasingly technologically driven world. The study advocates ongoing comparative analyses to glean insights and identify best practices conducive to fostering educational excellence amid the evolving technological landscape.